NTU camps’ preparation platform - Tan, Ting Hwee (2018)
The Freshmen Orientation Week is a 2 weeks period that holds great importance for freshmen to prepare for University, and make important connections. Every year, the Freshmen Orientation Camps of various faculties are organized by student volunteers. The two main factors contributing the success of Freshmen Orientation Programmes are the booking of facilities to host events and the booking of hostels for student. As of current, the allocation of facilities to various Freshmen Orientation Programmes is done using a Google Docs spreadsheet. Once the allocation is confirmed, it is difficult to make future amendment. In several occasions, the procedure for additional booking of facilities were not clear and request for bookings were not processed or reflected in the spreadsheet. Since 2016, Nanyang Technological University offers hostel stay services for the various Freshmen Orientation Programmes. To provide a complete and unique experience to all freshmen, most of the FOPs will opt for overnight accommodations. However, the process of requesting for hostel services can be error-prone, largely due to ineffectiveness of the current system. This Final Year Project focuses on improving the planning experience of all the parties involved in the Freshmen Orientation Program (FOP), using web application as an informative and secure communication channel. The idea of this approach is to have a one-stop platform that provides timely updates, a single point of contact for discussions, request application for resources and ease of access to information.